Geographical Concentration and Editorial Favoritism within the Field of Laboratory Experimental Economics - Janis Cloos; Matthias Greiff; Hannes Rusch (ZBW - Leibniz Information Centre for Economics, 2020)
We examine geographical concentration, scientific quality, and editorial favoritism in the field of experimental economics. We use a novel data set containing all original research papers (𝑁 = 583) that exclusively used laboratory experiments for data generation and were published in the American Economic Review, Experimental Economics or the Journal of the European Economic Association between 1998 and 2018. The development of geographical concentration is examined using data on authors' affiliations at the time of the respective publication. Results show that research output produced by US-affiliated economists increased slower than overall research output, leading to a decrease in geographical concentration. Several proxies for scientific quality indicate that experiments conducted in Europe are of higher quality than experiments conducted in North America: European experiments rely on a larger total number of participants as well as participants per treatment, and receive more citations compared to experiments conducted in North America. Examining laboratory experiments published in the AER more closely, we find that papers authored by economists with US-affiliations receive significantly fewer citations in the first 5 and 10 years after publication compared to papers by authors from the rest of the world.
Keywords: A11; A14; C90; I23; 330; laboratory experiments; favoritism; geographical concentration; methodological standards; network effects